Assessing the impact of architecture efficiency on the business model competitiveness - Bortnik, A.; Martins, J. M.; Mata, M. N.; Boichenko, K.; Dantas, R. (Business: Theory and Practice, 2024)
The purpose of this research is to develop a methodological approach to assessing the impact of the architecture effectiveness of the enterprise business model on the level of its competitiveness. The study methodology suggests the author’s approach to assessing the architecture effectiveness and the level of enterprise competitiveness. The scenario approach was used in order to the evaluate the connection between competitiveness, business model potential and enterprise architecture based on the economic-mathematical method of solving the nonlinear optimization problem through the use of hierarchical synthesis. The study was conducted according to the materials from 15 private clinics in Ukraine. The analysis of the obtained indices of architecture efficiency, competitiveness and potential level of the business model of the private clinics under study was carried out. It is determined that the level and growth rates of the enterprise architecture efficiency of private clinics have significant distinctions, which affect the level of their competitiveness. A group of leading companies in terms of the level of business model potential is singled out based on the definition of the correlation between the level of business model potential and the enterprise architecture efficiency. It is established that the level of business model potential of private clinics is substantially dependent on the level of enterprise architecture efficiency. It is proved that the efficiency of enterprise architecture has a significant influence on the potential and competitiveness of the business model. The novelty of the study consists in the methodological approach to assessing the impact of business model architecture on the level of its competitiveness, taking into consideration the identification of functional rather than strictly parametric correlation between variables. This research can be useful for professionals, scientists and researchers involved in developing and implementing effective business models and designing the enterprise architecture in order to achieve the company’s strategic intentions and to create and maintain competitive market positions.